Direct Stiffness Energy Model for a One-Dimensional Complex System - Ichchou, M.N.; Jezequel, L. (Engineering Transactions, 2001)
This paper deals with the high frequency analysis of one-dimensional waveguides. In this frequency range, this paper proposes a numerical implementation and tests of an alternative to the classical predictive dynamical methods. The originality of this approach consists in the fact that it is solely an energy density description. A numerical scheme very similar to the well-known direct stiffness method is employed here. This leads to a numerical code capable of predicting the mean value energy density for complex beam-like structure up to high frequencies. A twenty four components plane truss, including both the bending and extension motion is used as a verification test, and shows the ability of the proposed code to predict the high frequency dynamics of complex beam-like structures.